Analisis Resepsi Penggemar NewJeans Terhadap Hubungan Parasosial dalam Video Musik Ditto (side A & side B) dan OMG - Fakhriyah, Fat'hiyyah 'Asya (Jurnal Ilmiah Wahana Pendidikan, 2024)
In parasocial relationships, the audience forms a joint relationship with the characters that are displayed in the media using imagination. A relationship based on imagination must have an impact on both audiences and celebrities. In order to be able to anticipate the impact of parasocial relationships, messages about parasocial relationships begin to be delivered, one through music videos. NewJeans' Ditto (side A & side B) and OMG music videos are among the music videos that convey messages about parasocial relationships. Although it is intended to convey messages of parasocial relationships, the messages in the music video are received differently by the fans. This study aims to determine NewJeans fans' reception to messages about parasocial relationships in Ditto (side A & side B) and OMG music videos. The research method used in this study is qualitative research with the approach of Stuart Hall's reception analysis. The data collection was carried out with in-depth interviews and documentation of New Jeans fans who have watched Ditto (Side A & Side B) and OMG music videos. The results of this study showed that NewJans fans are active audiences who have different receptions of messages about Parasocial Relationships in Ditto (side A & side B) and OMG music videos.